Crafting combinations to govern groundwater: Knowledge, motivation, and agency - Meinzen-Dick, Ruth S.; Bruns, Bryan (Ubiquity Press, Ltd., 2024)
Groundwater is a vital common pool resource for water supply, irrigation, and ecosystems, but can be difficult to govern due to invisibility, conflicting interests, and limitations of available institutions. While there are many policy and technical instruments (tools) available, efforts to apply them are often ineffective.